2014
DOI: 10.1002/pssr.201409017
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties and switching endurance of Hf0.5Zr0.5O2 films on TiN bottom and TiN or RuO2 top electrodes

Abstract: The effect of the top electrode (TE) on the ferroelectric properties and switching endurance of thin Hf0.5Zr0.5O2 films was examined. The TiN/Hf0.5Zr0.5O2/TiN capacitor can endure electric cycling up to 109 times, which is promising for the next‐generation memory. RuO2 TE was reduced during annealing due to the reactive TiN bottom electrode, resulting in the degradation of the ferroelectric properties and endurance. In addition, the endurance of the TiN/Hf0.5Zr0.5O2/TiN capacitors was optimized by changing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
113
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 19 publications
4
113
0
Order By: Relevance
“…10 The increase in E c in the O 2 -annealed sample, which can occur with the oxidation of TiN electrodes, was not observed too. 13 From the comparison of Fig. 3a and b, the increase in the P r and E c of HZO films can be observed by the wake-up cycling.…”
Section: Resultsmentioning
confidence: 84%
“…10 The increase in E c in the O 2 -annealed sample, which can occur with the oxidation of TiN electrodes, was not observed too. 13 From the comparison of Fig. 3a and b, the increase in the P r and E c of HZO films can be observed by the wake-up cycling.…”
Section: Resultsmentioning
confidence: 84%
“…Studies by Park et al even suggest a partial oxidation of the complete TiN. [41,42] Thus, the complete device stack consists of TiO x N y /TM-HfO x /FE-HfO 2 /TM-HfO x /TiO x sandwiched between two TiN electrodes, Figure 5b. Polycrystallinity of the HfO 2 layer was explicitly taken into account, creating the grain structure of the stack, as shown in Figure 5b.…”
Section: Modelingmentioning
confidence: 97%
“…The ESD of state-ofthe-art electrostatic capacitors with various material systems is wileyonlinelibrary.com monoclinic-or tetragonal-phase HfO 2 was not expected to show FE properties. [13][14][15][16][17][18][19] The unexpected FE properties were reported to have resulted from the formation of the noncentrosymmetric orthorhombic phase (o-phase, space group: Pbc2 1 ). It was recently reported that the o-phase can be formed when large tensile stress is asymmetrically applied along the caxis of the tetragonal phase (t-phase, space group: P4 2 /nmc) of Hf x Zr 1-x O 2 (HZO) fi lms.…”
Section: Doi: 101002/aenm201400610mentioning
confidence: 99%